Two basic properties of space representation in the brain: evidence from unilateral neglect. Issue 2 (February 1985) - Bisiach, E; Capitani, E; Porta, E
Abstract : It is argued, on the grounds of earlier findings, that the neural substrate of egocentric space representation has analogue (non-symbolic) topo-topical properties. It is then argued from fresh evidence that space representation appears to be anchored to the sagittal midplane of the trunk and to the line of sight. A tentative reduction of the suggested properties of space representation to the neuro-physiological level is briefly outlined.